Hierarchical Polyimide Nonwoven Fabric with Ultralow-Reflectivity Electromagnetic Interference Shielding and High-Temperature Resistant Infrared Stealth Performance - Tang, Xinwei; Lu, Yezi; Li, Shuangshuang; Zhu, Mingyang; Wang, Zixuan; Li, Yan; Hu, Zaiyin; Zheng, Penglun; Wang, Zicheng; Liu, Tianxi (Nano-Micro Letters, 2024)
Designing and fabricating a compatible low-reflectivity electromagnetic interference (EMI) shielding/high-temperature resistant infrared stealth material possesses a critical significance in the field of military. Hence, a hierarchical polyimide (PI) nonwoven fabric is fabricated by alkali treatment, in-situ growth of magnetic particles and "self-activated" electroless Ag plating process. Especially, the hierarchical impedance matching can be constructed by systematically assembling Fe3O4/Ag-loaded PI nonwoven fabric (PFA) and pure Ag-coated PI nonwoven fabric (PA), endowing it with an ultralow-reflectivity EMI shielding performance. In addition, thermal insulation of fluffy three-dimensional (3D) space structure in PFA and low infrared emissivity of PA originated from Ag plating bring an excellent infrared stealth performance. More importantly, the strong bonding interaction between Fe3O4, Ag, and PI fiber improves thermal stability in EMI shielding and high-temperature resistant infrared stealth performance. Such excellent comprehensive performance makes it promising for military tents to protect internal equipment from electromagnetic interference stemmed from adjacent equipment and/or enemy, and inhibit external infrared detection. Highlights: 1 Hierarchical polyimide (PI) nonwoven fabric is fabricated by alkali treatment, in-situ growth of magnetic particles, and "self-activated" electroless Ag plating process. 2 Impedance matching structure by assembling Fe3O4/Ag-loaded PI nonwoven fabric (PFA) and pure Ag-coated PI nonwoven fabric (PA) induces more electromagnetic waves enter PFA/PA and be dissipated. 3 The fluffy 3D space structure of PFA with strong adhesion interaction and low infrared emissivity of PA endow PFA/PA with excellent thermal stability in electromagnetic interference shielding and high-temperature resistant infrared stealth performance.